Myocardial stiffness assessed by shear wave elastography relates to pressure-volume loop derived measurements of chamber stiffness. (4th February 2022) - Bezy, S; Caenen, A; Duchenne, J; Orlowska, M; Amoni, M; Puvrez, A; D"hooge, J; Voigt, JU
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Research Foundations Flanders Background: Increased myocardial stiffness is an important cause of diastolic dysfunction. Currently, invasive pressure-volume loop analysis is the gold standard method for the assessment of the left ventricular (LV) chamber stiffness. Its non-invasive assessment in the clinic is cumbersome, requires the combination of several parameters and has limited reliability. Shear wave elastography (SWE) is a novel method that evaluates the propagation of shear waves travelling along the myocardium using high frame rate echocardiography. The propagation speed is directly related to myocardial stiffness. Shear waves can be induced naturally by mitral valve closure (MVC). So far, the in vivo validation of SWE against an invasive gold standard reference method is still lacking. Purpose: To compare myocardial stiffness assessed by shear wave propagation speed after MVC to invasive pressure-volume loop derived measurements of chamber stiffness. Methods: Fifteen pigs (31.2 ± 4.1 kg) were included in the study. The instantaneous stiffness of the myocardium was altered by performing the following interventions: 1) preload reduction, 2) afterload increase, 3) preload increase and 4) induction of ischemia/reperfusion (I/R) injury by balloon occlusion of the proximal LAD for 90 min. with subsequent reperfusion of 40 min. To obtain the end-diastolic pressure-volume loop relation (EDPVR), a set of pressure-volume loops was acquired under preload reduction. From the EDPVR, the chamber stiffness constant β and operating chamber stiffness dP/dV were derived. SWE datasets in a parasternal long-axis view were acquired with an experimental ultrasound scanner at an average frame rate of 1304 ± 115 Hz. Shear waves after MVC were visualized on tissue acceleration maps by drawing an M-mode line along the interventricular septum (Figure 1A). The propagation speed was calculated by semi-automatically measuring the spatiotemporal slope. Results: The chamber stiffness constant β significantly increased after the induction of the I/R injury (0.05 ± 0.01 1/ml vs. 0.09 ± 0.03 1/ml; p < 0.001). The operating chamber stiffness dP/dV decreased by reducing preload and increased by increasing afterload, increasing preload or by inducing an I/R injury (0.50 ± 0.18 mmHg/ml vs. 0.09 ± 0.05 mmHg/ml, 0.67 ± 0.19 mmHg/ml, 0.78 ± 0.35 mmHg/ml and 1.09 ± 0.38 mmHg/ml, respectively; p < 0.01). Likewise, shear wave propagation speed after MVC increased by increasing pre- and afterload (p = 0.001) and by inducing I/R injury (p < 0.001) (Figure 1B). Preload reduction had no significant influence (p = 0.118). Shear wave speed had a strong positive correlation with β (r = 0.63; p < 0.001) (Figure 1C) and dP/dV (r = 0.81; p < 0.001) (Figure 1D). Conclusions: Shear wave speed after MVC is strongly related to invasive pressure-volume loop derived measures of chamber stiffness. The results of this study indicate the potential of SWE as a novel non-invasive method for the assessment of the instantaneous stiffness of the myocardium.